EFFECT OF COMBINATION OF GnRH AND PGF2α FOR ESTRUS SYNCHRONIZATION ON ONSET OF ESTRUS AND PREGNANCY RATE IN DIFFERENT POSTPARTUM IN SWAMP BUFFALO IN KAMPAR REGENCY - Yendraliza, Y.; Zesfin, B.P.; Udin, Z.; Jaswandi, J.; Arman, C. (Diponegoro University, 2011)
The purposes of this study were to investigate the effect of administration of GnRH and PGF2α ononset of estrus and conception rate in different postpartum swamp buffalo (Bubalus bubalis). Twentypostpartum (pp) buffalo-cows were divided into four groups of five buffaloes as follows: Group A (30day pp), Group B (45 dpp), Group C (60 dpp), and Group D (75 dpp). The buffaloes in each group wereinjected intramuscularly with 3 ml GnRH at day 0, followed by intramuscular injection of 2.5 ml PGF2α,10 ml) at day 7 after GnRH injection. Observation of estrus was performed 24 h after injection of PGF2α.Artificial insemination was performed 18 h after estrus signs clearly visible. The result of study showedthat there were no difference (p>0.05) among treatments on the percentages of estrus (100%), onset ofestrus (37.4 to 38.4 h), duration of estrus (16.8 to 18.2 h) and conception rate (100%). In conclusion,buffalo-cows in Kampar Regency can be served as early as 30 days post partum using combination of 3ml GnRH and 2.5 ml of PGF2α.